2016
DOI: 10.7314/apjcp.2016.17.4.1729
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between RAS Test Results and Prognosis of Metastatic Colorectal Cancer Patients: a Report from Western Iran

Abstract: In the patients with metastatic colorectal cancer (mCRC), RAS testing is the first step to identify those that could benefit from anti-EGFR therapy. This study examined associations between KRAS mutations and clinicopathological and survival data in Iranian patients with mCRC. Between 2008 to2015 in a retrospective study, 83 cases of mCRC were referred to the Clinic of Medical Oncology. The mean follow-up was 45 months that there were 27 deaths. The 3 patients that did not complete follow-up were censored from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
5
13
2
Order By: Relevance
“…All studies included 1814 CRC patients that mean age of the patients was 57.5 years. In more studies, the prevalence of CRC in males was more than females (Amirifard et al, 2016;Bishehsari et al, 2006;Dolatkhah et al, 2016;Naseri et al, 2016;Omidifar et al, 2015;Payandeh et al, 2016;Roudbari et al, 2016;Shemirani et al, 2011;Tameshkel et al, 2016;Vakil et al, 2016). Number of mutations in codon 12 and 13 and also mutant amino acid in codon 12 has been shown in Table 1 that Gly is normal amino acid in codon 12 and can change to other amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies included 1814 CRC patients that mean age of the patients was 57.5 years. In more studies, the prevalence of CRC in males was more than females (Amirifard et al, 2016;Bishehsari et al, 2006;Dolatkhah et al, 2016;Naseri et al, 2016;Omidifar et al, 2015;Payandeh et al, 2016;Roudbari et al, 2016;Shemirani et al, 2011;Tameshkel et al, 2016;Vakil et al, 2016). Number of mutations in codon 12 and 13 and also mutant amino acid in codon 12 has been shown in Table 1 that Gly is normal amino acid in codon 12 and can change to other amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…All studies are case-control studies published between 2006 and 2016. Six studies were studied from Tehran (Central of Iran) (Bishehsari et al, 2006;Roudbari et al, 2016;Shemirani et al, 2011;Sobhani et al, 2010;Tameshkel et al, 2016;Vakil et al, 2016), one study from Shiraz (Southwest of Iran) (Omidifar et al, 2015), two studies from Kermanshah (Western of Iran) (Amirifard et al, 2016;Payandeh et al, 2016), one study from Tabriz (Northwestern of Iran) (Dolatkhah et al, 2016), and one study from South Khorasan (Eastern of Iran) (Naseri et al, 2016). All studies included 1814 CRC patients that mean age of the patients was 57.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge only two published studies have been reported from Iran about the frequency of NRAS in KRAS and BRAF mutation negative CRCs. 17 , 18 In this study, we want to identify NRAS mutations rate and spectrum (at codons 12, 13, and 61) in 52 KRAS and BRAF wild type during 5 years (2011-2015) in the hospitals affiliated to Shiraz University of Medical Sciences as the largest referral center in south of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that these mutation types may confer more aggressive phenotype due to the functional differences associated with different amino acid substitutions, and then resulting protein from these mutation types. Our reported novel KRAS mutation G10V had the same amino acid change, but the prognosis of the patient was not as poor as their report and he had a good response to treatment [6,12]. Further experimental and cohort studies about any association between different KRAS mutation types and biological behaviors are needed to substantiate this theory.…”
Section: Discussionmentioning
confidence: 52%